2017
DOI: 10.1084/jem.20161707
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 signaling drives macrophage-induced adaptive immune suppression in pancreatic carcinoma

Abstract: Daley et al. show that NLRP3 signaling in macrophages drives their immune-suppressive phenotype in the pancreatic tumor microenvironment and potentiates tolerogenic T cell differentiation. Conversely, targeting NLRP3 protects against pancreatic oncogenesis and is associated with immunogenic reprograming within the tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
150
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(159 citation statements)
references
References 48 publications
(69 reference statements)
9
150
0
Order By: Relevance
“…Inflammasome components are expressed not only by immune cells (e.g., macrophages) but also by non-immune cell types, including acinar and cancer cells. Previous studies indicated that activation of NLRP3 and AIM2 inflammasome contributes to pancreatitis (Hoque et al, 2011;Kang et al, 2016a) and that activation of the NLRP3 inflammasome within macrophages entails immune suppression in pancreatic cancer development (Daley et al, 2017). Here, we demonstrate that mitochondrial iron-mediated oxidative DNA injury results in AIM2 inflammasome activation in PDAC cells, which in turn induces HMGB1 release and subsequent CD274 expression.…”
Section: Discussionsupporting
confidence: 59%
“…Inflammasome components are expressed not only by immune cells (e.g., macrophages) but also by non-immune cell types, including acinar and cancer cells. Previous studies indicated that activation of NLRP3 and AIM2 inflammasome contributes to pancreatitis (Hoque et al, 2011;Kang et al, 2016a) and that activation of the NLRP3 inflammasome within macrophages entails immune suppression in pancreatic cancer development (Daley et al, 2017). Here, we demonstrate that mitochondrial iron-mediated oxidative DNA injury results in AIM2 inflammasome activation in PDAC cells, which in turn induces HMGB1 release and subsequent CD274 expression.…”
Section: Discussionsupporting
confidence: 59%
“…Thus, our data make a compelling case that pomalidomide-induced downregulation of IRF4 may reprogram macrophage populations in the pancreas to an inflammatory phenotype. However, futures studies should investigate if pomalidomide can also regulate other factors that control TAMinduced adaptive immune suppression in PDA, such as NLRP3/ IL10 signaling (39), or factors of the necrosome such as RIP3 and Mincle (40).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation affects all stages of tumorigenesis and the key signaling pathway triggering inflammation is to activate inflammasome, which lead to inflammatory responses . NLRP3 inflammasome, a protein complex composed of NLRP3, ASC, and caspase‐1, contributes to its biological function in the pathogenesis of cancers, such as oral squamous cell carcinoma, lymphoma, and pancreatic carcinomas . However, its specific role in inflammation‐related lung carcinogenesis has not yet been explored.…”
Section: Discussionmentioning
confidence: 99%